Recria de bezerras de corte sob pastejo exclusivo em azevém ou em azevém consorciado com leguminosas - Vicente, Juliano Melleu (2017)
The ingestive behavior and the ingestion of forage by beef heifers were evaluated in the vegetative and flowering stages of ryegrass (Lolium multiflorum L.). The treatments were: grazing exclusively on ryegrass, ryegrass intercropping with vetch (Vicia sativa L.) or red clover (Trifolium pratense L.). The grazing method was continuous with variable stocking. The experimental design was the completely randomized with repeated measures arrangement, three forage systems and three repetitions of area. For evaluations of forage intake, chromic oxide was used as an indicator of fecal production and heifers were considered as experimental units. The forage mass, allowance of forage and allowance of leaf blades were, 1596.2 kg / ha DM, 12 kg DM / 100 kg BW and 4.5 kg DM / 100 kg BW respectively. The participation of vetch and red clover in the forage mass corresponded to 13.2% and 4.5% respectively in the vegetative stage. In the flowering stage, the participation of legumes corresponded to 0.6%. In forage as grazed, crude protein (17.8%), neutral detergent fiber (55.8%) and in situ dry matter digestibility (76.7%) were similar among forage systems. These variables differed between phenological stages of ryegrass. The grazing time differed between the systems being superior in the system with vetch. The forage intake rate in the clover system was higher than the other systems. The dry matter intake was similar among forage systems and was higher in the vegetative stage compared to the flowering stage. The average daily gain was similar among forage systems and phenological stages. With little participation of red clover or vetch in the herbage mass intercropped with ryegrass, it does not modify the intake of dry matter, crude protein and neutral detergent fiber, resulting in the same performance of beef heifers.